Goat Cattle Fattening Business Group in Naga Jaya I Village Bandar Huluan District - Farida, Farida Ariani; Tugiman, Tugiman; Hasdari, Hasdari Helmi Rangkuti; Sarjana; Ramadhan, Muhammad Ramadhan (Talenta Publisher, 2021)
Goat fattening business is a line of business that has good prospects in the future. The need for goat meat that continues to increase from year to year is not matched by the growth of good livestock centers. Naga Jaya I Village is one of many villages where many people develop goat farming businesses. Some of the reasons people develop this business are the seed capital which is not too expensive compared to cattle or buffalo and the relatively short cycle of breeding (n < 1 year). In the midst of a fairly good business prospect, service partners in this activity still have classic obstacles in business development. The problems faced are capital, availability of technology for animal feed processing, small business management and management of the cage environment. Based on the problems faced by service partners, this activity is planned to be carried out with the aim of overcoming technological and management obstacles. The service team will provide solutions to these two problems by providing grass chopper/animal feed machines and increasing partner knowledge about the management of the enclosure environment through outreach activities. At the end of the activity, it is hoped that the productivity of partners will increase which is reflected in changes in feeding methods and environmental management behavior.